DYSFUNCTIONAL BELIEFS AND ATTITUDES ABOUT SLEEP IN UNDERGRADUATE MEDICAL AND DENTAL STUDENTS - Ain, Noor ul; Ahmad, Habiba; Rehman, Sana; Emman, Sarah; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the association of dysfunctional beliefs and attitudes about sleep with sleep quality in undergraduate medical and dental students. Methodology: This was a cross sectional study which included undergraduate medical and dental students of Peshawar, conducted from December 2018 to March 2019. Participants were asked to fill out Dysfunctional beliefs about sleep scale (DBAS-16) and Pittsburgh sleep quality index (PSQI) to determine the type of individual beliefs and attitudes about sleep and quality of sleep. The data were analysed using SPSS version 25. Chronbach's alpha was used to measures reliability of the scales. Chi square test was applied to find out the relationship between quality and expectations about sleep and also to find difference in both based on gender and institute, considering a p-value of <0.05 to be significant. Results: The mean age of the sample (n=1199) was 20.90 ± 1.98 years. Majority of the students were females (n= 742, 61.9%). Unrealistic expectations about sleep were reported by 1060 (88.4%) students on DBAS and 1119 (93.3%) reported poor sleep quality on PSQI. Regarding expectation about sleep, no significant difference was observed in terms of gender and institutes using chi-square test (p=.850 and .363 respectively). However, female students showed significantly poor sleep quality (p=.000) as compared to male students. Conclusion: The study concluded that a large number of medical and dental students have dysfunctional beliefs about sleep which leads to poor quality of sleep.